Application of Artificial Intelligence to the Development of Playing Ability in the Valorant Game - Fernanda, Adwita; Fadri Geovanni, Abid Renata; Huda, Miftahul (Pandawan Sejahtera Indonesia, 2022)
From children to adults, everyone enjoys playing online games as a form of entertainment. Online games have a more popular market because they can meet other players worldwide connected to the internet. NPCs (players controlled by a computer system) are also available in online games as player substitutes or for skill practice. As a result, we have been interacting with artificial intelligence in the competition and our environment without realizing it. The game's AI (Artificial Intelligent) can offer an experience similar to playing with other players. Artificial intelligence may always influence online games, whether to replace opponents or choose the game's plot. First Person Shooter (FPS) game Valorant was made available for free on the Windows platform by Riot Games. With a CS: GO-like concept (Counter Strike Global Offensive). The amount of money you have available for each round must be calculated at the equipment purchasing phase to produce effective gaming equipment. The Greedy Algorithm is one of the algorithms that can be used to choose the equipment for the money/cred owned. This algorithm will select the most expensive item the player can buy each round so that the player's chances of winning that round increase.